Towards Implementing the Grameen Bank Financing Model Among Micro Enterprises in Botswana: Is it a Possibility? - Mutoko, Wilbert R.; Mutoko, Phillis (European Scientific Journal, ESJ, 2020)
Micro Enterprises (MiEs) in Botswana are neglected by financial institutions in favor of Small and Medium Enterprises (SMEs) that have collateral security and financial records. MiEs could engage unemployed youths and adults to become self-employed and alleviate poverty; but MiEs struggle to finance their businesses because financial institutions require business proposals and collateral security; furthermore, micro lenders charge exorbitant interests. Currently there is no study specifically targeting MiEs financing in Botswana tailoring the Grameen Bank Model (GBM), hence the need for this study. This research explores how financial institutions can adopt the GBM from Bangladesh to finance Botswana MiEs. Apart from literature search, interviews were conducted among three commercial banks in Gaborone, Botswana to explore the banks’ awareness and willingness to apply the GBM in Botswana. Purposive sampling was used to select the three banks out of seven, in 2015. Findings show that commercial banks are not ready to accept the GBM as they fear losing money through defaulting customers. It is hoped that the findings will shed light on challenges and opportunities of implementing GBM in Botswana, and the possibility of applying it to reduce unemployment and alleviate poverty. It is recommended that Botswana Government invites Professor Yunus, Grameen Bank founder, to come and hold a workshop for bankers and other stakeholders; introducing GBM and its possible benefits to Botswana. The researchers recommend that local financial institutions should develop funding packages specifically for MiEs to grow their businesses.